Efficient removal of Pb(II) ions by using 2-acetylthiophene-modified graphene oxide from aqueous solution. (December 2022) - Guo, Y.; Wu, D.F.; Wu, H.M.; Liu, X.Y.; Xu, H.Z.; Chen, Q.Q.
Abstract: A novel Schiff's base functionalized graphene oxide (A-GO) was synthesized for removal of Pb(II) ions from aqueous solution. Two-step fabrication route, including silylation process of graphene oxide by 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane (N-GO) and Schiff's base reaction of N-GO with an organic ligand of 2-acetylthiophene (A-GO) was carried out. The surface morphology, material structure, chemical states and elemental distribution of A-GO were characterized by means of XRD, SEM, EDXS, TEM, Raman, TGA, FTIR and XPS. The introduction of Schiff's base ligand increased the interlayer spacing and created some vacancies and topological defects of A-GO, which made excellent contact with the Pb(II) solution. Moreover, the functional organic groups on A-GO played an important role in the adsorption of Pb(II) ions. The adsorption behavior of Pb(II) ions onto A-GO was systematically investigated. The A-GO adsorbent exhibited a high adsorption capacity of 408 mg/g on Pb(II) ions. The analyses of adsorption isotherms and kinetics revealed that the Langmuir isotherm model and Pseudo-second-order kinetic mode can well describe the adsorption behavior of Pb(II) ions with A-GO. In addition, thermodynamic parameters indicated that the adsorption process was spontaneous and endothermic. Adsorption mechanism analyses suggested that the –NH2 and –C=S functional groups on A-GO have strong chemical combination ability with Pb(II) ions through coordination bonds to enhance the adsorption capacity. Furthermore, the A-GO materials can be reused five times without significantly losing adsorption capacity. Therefore, the prepared A-GO adsorbent is a potential material for Pb(II) elimination from aqueous solution. Graphical abstract: Image 1 Highlights: A 2-acetylthiophene-modified graphene oxide (A-GO) was successfully synthesized by Schiffs' base reaction. The A-GO processed excellent adsorption properties for Pb(II) ions from aqueous solution. The functional organic groups on A-GO played an important role in the adsorption of Pb(II) ions. The A-GO material shows good reusability.